2018
DOI: 10.1093/jas/sky367
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of exogenous butyrate on the gastrointestinal tract of sheep. I. Structure and function of the rumen, omasum, and abomasum1

Abstract: The aim of this study was to determine the effect of exogenous butyrate on the structure and selected functions of the stomach in sheep. Eighteen rams (30.8 ± 2.1 kg; 12 to 15 mo of age) were allocated to the study and fed a diet for 14 d without (CTRL) or with sodium butyrate (BUT; 36 g/kg of offered DM). Neither DMI nor initial BW differed between treatments (P ≥ 0.61), but final BW was greater for BUT compared with CTRL (P = 0.03). Butyrate concentration in the reticuloruminal fluid and abomasal digesta was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…About 15% of ruminal short-chain fatty acid will flow to the omasum, abomasum, and SI (Górka et al, 2018b,c). Butyrate can then be absorbed by the omasum (Rupp et al, 1994;Górka et al, 2018c) or SI (Górka et al, 2018b). Górka et al (2011b) found that calves supplemented with unprotected SB in TMR had increased mitotic indices and decreased apoptotic indices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 15% of ruminal short-chain fatty acid will flow to the omasum, abomasum, and SI (Górka et al, 2018b,c). Butyrate can then be absorbed by the omasum (Rupp et al, 1994;Górka et al, 2018c) or SI (Górka et al, 2018b). Górka et al (2011b) found that calves supplemented with unprotected SB in TMR had increased mitotic indices and decreased apoptotic indices.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2006 the European Union put a ban on antibiotic-like growth promoters (European Commission, 2005). An additive that has been shown to cause growth promotion that could replace ionophores is sodium butyrate (SB; Górka et al, 2018c;Rice et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the emergence of RNA-seq as an approach for the study of physiological changes in human and model organisms [ 8 ], application of transcriptome analysis in the stomach of ruminant has been expanding [ 9 ]. On the one hand, researchers focused on obtaining a more complete understanding of the molecules and pathways in rumen papillae between low and high feed efficiency in adult beef cattle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies evaluated the effects of different feeding strategies on the structure and function of the abomasum in cattle. For example, previous studies demonstrated that ruminal butyrate [ 9 ] and the increased proportion of dietary concentrate [ 13 ] may affect not only the rumen but also other parts of the GIT, such as the omasum, abomasum, and proximal small intestine. The microbiota within the four stomachs in ruminant could pass from one segment to another with the digest [ 7 ].…”
Section: Introductionmentioning
confidence: 99%